Pushing limits: the role of pain and painkillers in Olympic weightlifting - Schneider, Sven; Hörner, Helene; Schmitt, Holger; Berrsche, Gregor (Sportverletzung, Sportschaden, 2025)
The PLAY study (Pain, Lesions and Analgesics in Youth and Elite Sports) investigates the extent, patterns and treatment of pain in organised professional sports. This study, presented here for the first time, focused on Olympic weightlifting in this context. As part of a case-control study, weightlifters from the German Olympic squad (OSW, n=35) were compared with matched controls from the general population (n=35) using 1:1 matching for sex, age, and BMI. Validated, field-tested questions and scores were used to record the prevalence of pain, analgesic consumption and willingness to compete despite pain among German elite athletes. Due to the matched pairs design, bivariate associations were examined using McNemar tests. Among the 35 Olympic weightlifters surveyed, 80% (8 out of 10) reported experiencing pain in the past 7 days, with an average of at least 3 regions affected simultaneously, mainly neck, back, head, and knees. With the exception of the back (71% vs. 83%; p>0.05), the 12-month pain prevalence was significantly higher in OSW, especially in the wrists (66% vs. 40%; p=0.035), where the most severe pain occurred (VAS 7.3/10). The use of painkillers was widespread among athletes and controls. Among Olympic weightlifters, the majority of cases involved self-medication. Frequent consumption was mainly found for ibuprofen (20%), acetylsalicylic acid (14%), and diclofenac (9%). The willingness to take part in competitions despite pain was widespread among the top athletes in our sample: 94% stated they would take part even if they needed to take painkillers. In contrast, only 9% reported that they would continue to participate even if their doctors advised against it. Therefore, doctors seem to act as gatekeepers and are most likely able to dissuade athletes from making such risky decisions. Among the athletes studied here at the highest national performance level, high 12-month prevalence rates for joint pain, widespread and, in some cases, prophylactic self-medication with painkillers were observed, along with a strong willingness to compete despite health complaints and pain.